2015
DOI: 10.4236/aim.2015.52009
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Induction of Lignin Peroxidase in Manganese-Deficient Cultures of the White Rot Fungus <i>Phanerochaete chrysosporium</i>

Abstract: The lignin peroxidase (LIP) production and regulation, in manganese ions (Mn 2+ ) deficient cultures of the white rot fungus Phanerochaete chrysosporium, is still not clearly understood. Mn 2+ deficiency is correlated to low levels of manganese containing superoxide dismutase (MnSOD). In this work, we show that despite the low activity level of MnSOD in Mn 2+ -deficient cultures, the presence of H 2 O 2 is essential for the expression of the lip-H2 gene, which encodes for the major LIP isoenzyme produced (LIP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Other WSC domain-containing glyoxal oxidases (from F. verticillioides and F. oxysporum) have been previously studied, and they had similar effects on pathogenicity (Crutcher et al 2019). One of the known functions of GLOX is participating in the degradation of lignin by providing H 2 O 2 for the oxidation reaction catalyzed by extracellular peroxidase (Kersten et al 1995;Bak et al 2009;Takano et al 2010;MacDonald et al 2011;Kersten & Cullen 2014;Matityahu et al 2015;Kadowaki et al 2018;Wohlschlager et al 2021). Therefore, to explain the pathogenicity defect of CsGLOX gene mutants, we suggest that H 2 O 2 production by CsGLOX activity may be one of the necessary requirements for infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other WSC domain-containing glyoxal oxidases (from F. verticillioides and F. oxysporum) have been previously studied, and they had similar effects on pathogenicity (Crutcher et al 2019). One of the known functions of GLOX is participating in the degradation of lignin by providing H 2 O 2 for the oxidation reaction catalyzed by extracellular peroxidase (Kersten et al 1995;Bak et al 2009;Takano et al 2010;MacDonald et al 2011;Kersten & Cullen 2014;Matityahu et al 2015;Kadowaki et al 2018;Wohlschlager et al 2021). Therefore, to explain the pathogenicity defect of CsGLOX gene mutants, we suggest that H 2 O 2 production by CsGLOX activity may be one of the necessary requirements for infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is a carbohydrate-active enzyme belonging to the "auxiliary activities" subfamily AA5_1 (Koschorreck et al 2022;Fong & Brumer 2023) and catalyze the oxidation of aldehydes into carboxylic acids while reducing dioxygen to hydrogen peroxide (H 2 O 2 ) (Kersten & Cullen 2014;Daou & Faulds 2017;Koschorreck et al 2022;Fong & Brumer 2023). It was further reported that GLOXs from wood-rot fungi participate in the degradation of lignin by providing H 2 O 2 for the oxidation reaction catalyzed by extracellular peroxidase (including lignin peroxidase, manganese peroxidase, and other multifunctional peroxidases) (Kersten et al 1995;Bak et al 2009;Takano et al 2010;MacDonald et al 2011;Kersten and Cullen 2014;Matityahu et al 2015;Kadowaki et al 2018;Wohlschlager et al 2021). Only a few GLOX genes in phytopathogenic fungi have been identified and functionally verified to be involved in the regulation of filamentous growth and pathogenic development; however, its molecular mechanism is still largely unknown (Kan et al 2004;Leuthner et al 2005;Song et al 2016).…”
Section: Original Papermentioning
confidence: 99%
“…Phanerochaete chrysosporium is widely known for its industrial use as a white rot fungus that breaks down the aromatic polymer lignin and thus is important in the degradation of wood products (Kersten and Cullen 2007 ; Matityahu et al 2015 ). Recently, Phanerochaete chrysosporium was confirmed as a member of the genus Phanerochaete s. str.…”
Section: Additional Names To Be Protectedmentioning
confidence: 99%
“…Phanerochaete chrysosporium is known to degrade lignin and various aromatic pollutants during secondary metabolism in the stationary phase. Peroxidases (manganese peroxidase and lignin peroxidase) and the extracellular H 2 O 2 -producing enzyme system of oxidase produced by these organisms are the main enzymes involved in the metabolism of lignin degradation, synthesized in response to the limited levels of nitrogen, carbon, and sulfur; also adopted various metabolic strategies to degrade complex polymeric substrates [1][2][3][4][5]. Many studies have shown that the type of strain and medium culture conditions affected the type of isoenzyme of LiP produced.…”
Section: ■ Introductionmentioning
confidence: 99%